Treatment of Venous Thromboembolism in Trauma Patients: Features and Possibilities - Khrebtiy, Yaroslav V.; Chernukha, Larisa M.; Skupyy, Oleh M.; Maiko, Viacheslav M.; Khrebtii, Halyna I. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. Treatment of venous thromboembolism continues to be one of the most controversial problems of modern angiology. This issue is especially relevant in the treatment of patients with traumatological pathology. Methods. Treatment of 1915 patients with fractures of lower extremities from 2017 to 2022 at the Vinnytsia Regional Pyrohov Clinical Hospital was analyzed. During the study period, 727 (38%) deep vein thromboses were diagnosed. Results. During the study period, 4 (0.2%) pulmonary embolisms were diagnosed, among which 3 (0.15%) were fatal. In 99.5% of patients with venous thrombosis and injuries, it was possible to achieve clinical improvement and regression of the thrombotic process. Conclusions. Treatment tactics for trauma patients with venous thromboembolism should be individualized and take into account the severity and localization of the injury, the need and urgency of trauma surgery, the risk of pulmonary embolism.